Kelelahan Kerja Pada Penenun Etnis Bugis Dalam Perspektif K3 - Fatmawaty Mallapiang; A. Syamsiah Adha (Direktorat Politeknik Kesehatan Makassar, 2023)
Weavers have various work risks in weaving in the form of fatigue effects which can be caused by monotonous work postures for long periods of time. The purpose of this study was to determine work fatigue and its management according to local perceptions of ethnic Bugis weavers in OHS perspective. This research is an analytic descriptive study related to work fatigue in weavers. Subjective measurement of work fatigue uses the Japan Industrial Fatigue Research Committee (IFRC) questionnaire, including measurements of weakening activities, weakening of motivation, and physical fatigue of workers. consisting of 30 point statements. Sampling in this study used a total sampling technique, namely the entire population as a sample of 141 respondents. Data analysis used descriptive analysis and chi-square with α=0.05. The results showed that 7 weavers (5%) experienced very high fatigue, 87 weavers (61.7%) experienced high fatigue, and 47 weavers (33.3%) experienced moderate fatigue. As for the treatment of fatigue based on local wisdom that is usually done is massaged by a family member or massage therapist (22.6%), taking herbal medicine (7.8%), and just letting it go (18.4%). For future researchers, they can examine the effectiveness of fatigue recovery based on local wisdom that has been practiced so far. Keywords : Fatigue, Weavers, Bugis Ethnic, OHS